Comparison of anthropometric characteristics and sprint start performance between elite adolescent and adult sprint athletes - Aerenhouts, D.; Delecluse, C.; Hagman, F.; Taeymans, J.; Debaere, S.; Van Gheluwe, B.; Clarys, P. (European Journal of Sport Science, 2012)
The aim of this study was to examine the physical characteristics and somatotype of junior and senior athletes in relation to sprint start and acceleration performance. Nineteen female junior, 23 male junior, 9 female senior, and 16 male senior sprint athletes performed three maximal 20-m sprints. The starting blocks were instrumented to measure forward propulsion forces. Running velocity was measured by a laser positioned behind the athlete at 1 m height. Anthropometric measures were used to calculate somatotype and skeletal muscle mass. Body composition was estimated by underwater weighing densitometry. Junior and senior athletes were of similar height in both sexes. Male seniors were heavier, had larger limb circumferences, and a higher skeletal muscle mass than male juniors. Only the limb circumferences of the female seniors were larger than those of the female juniors. Female juniors were balanced ectomorphs, while female seniors were situated centrally on the somatochart (2.7-2.2-3.9 vs. 2.6-3.1-3.1; P=0.772, 0.047, and 0.066 respectively). Male juniors were mesomorphic ectomorphs, while male seniors were ectomorphic mesomorphs (1.8-3.3-3.6 vs. 1.6-4.2-2.8; P=0.148, 0.002, and 0.002 respectively). All sprint starts were similar for the junior and senior athletes of both sexes. Senior athletes accelerated more than the junior athletes, which resulted in higher running velocities after 5 m (senior vs. junior: females, 5.51±0.32 vs. 6.01±0.27 m · s-1, P=0.001; males, 5.85±0.38 vs. 6.13±0.44 m · s-1, P=0.043). The greater muscularity of senior compared with junior athletes did not result in better sprint start dynamics, but they did accelerate more and ran faster. These results show that late-adolescent boys in particular are still developing their muscularity. The technical complexity of the sprint start and the negative influence of a higher body mass may partly explain the comparable sprint start dynamics of the junior and senior athletes. We suggest that strength training should be combined with sufficient attention to technical skills to allow a positive transfer.